Superb Microvascular Imaging for Detecting Ovarian Vascularity in Precocious Puberty, Premature Thelarche, and Pubertal Girls - Akyel, Nazlı Gülsüm; Mengen Uçaktürk, Eda; Sivri, Mesut; Alımlı, Ayşe Gül; Akmaz Ünlü, Havva; Uçaktürk, Seyit Ahmet (Cerrahpaşa Medical Journal, 2024)
Objective: We aimed to evaluate ovarian vascularity with superb microvascular imaging (SMI) and to compare it with other conventional Doppler imaging methods in girls with premature thelarche, precocious puberty, and those at puberty. Methods: A total of 133 ovaries from 69 patients were evaluated. Among the 69 subjects, 50 girls applied with the preliminary diagnosis of precocious puberty, and 19 of them were pubertal adolescent girls. The color Doppler imaging (CDI), power Doppler imaging (PDI), color SMI (cSMI), and monochrome SMI (mSMI) techniques were performed, and the images at the same site of the ovary were obtained. The images were evaluated by 2 pediatric radiologists using a 4-level grading system to evaluate the degree of vascularity. Results: A total of 69 patients were evaluated, including 19 who were pubertal, 39 with premature thelarche (PT), and 11 with precocious puberty (PP) were evaluated. Among the 50 patients, 11 were diagnosed with precocious puberty, while 39 received a diagnosis of premature thelarce. The sensitivity of the techniques according to vascularity grading was interpreted as mSMI > cSMI > PDI > CDI. The interrater agreement of vascularity grading among the two observers according to their κ values was almost perfect in the left CDI, left PDI, and right PDI (κ > 0.92), strong in the right CDI, left and right cSMI, left and right mSMI (κ > 0.80), and moderate in the right CDI (κ > 0.60). There was a significant difference between the vascularity of pubertal and prepubertal ovaries, which correlated with their volumes (P < .001). Ovarian vascularity was similar in precocious puberty and premature thelarche groups. Conclusion: The SMI is superior to other Doppler methods, such as PDI and CDI, in the evaluation of ovarian vascularity. It is useful in evaluating parenchymal vascularity, especially in pediatric patients. Cite this article as: Gülsüm Akyel N, Mengen Uçaktürk E, Sivri M, Gül Alımlı A, Akmaz Ünlü H, Uçaktürk SA. Superb microvascular imaging for detecting ovarian vascularity in precocious puberty, premature thelarche, and pubertal girls. Cerrahpaşa Med J. 2024;48(2):172-178.